Carcinoma en cuirasse: The body shield that has grave prognosis - Manjunath Hulmani1 , Harish Mallela2 , Linganagouda S Patil3 , Jagannath Kumar V4 (Perspectives In Medical Research, 2017)
Carcinoma en cuirasse is a rare form of cutaneous metastasis. Like other cutaneous metastasis, Carcinoma en cuirasse signifies advanced malignant disease with poor prognosis and short survival. We report a 45 year old woman, known case of infiltrating ductal carcinoma of the right breast and had received treatment with neoadjuvant chemotherapy followed by surgery, presented with seven month history of progressive appearance of multiple nodular lesions on the chest. Diagnosis of carcinoma en cuirasse was made based on clinical and histopathological features. Cutaneous metastasis signifies the persistence of primary cancer after treatment, and dramatically alters the therapeutic plans. Due to the high incidence of cutaneous manifestations of breast carcinoma, every practitioner should be highly suspicious of any acuteonset, persistent, firm papulonodules, especially on the chest